The importance of holistic assessment in palliative end-of-life care and quality health outcomes - Suantak Demkhosei Vaiphei (National Scientific Medical Center, 2019)
The present increasing numbers in terminal illness and chronic diseases gave rise to the importance of holistic assessment in the Indian clinical settings. Though being in the era of advance modern medicine and its components, people still die in distress as their mental disharmony and psychological suffering is not considered as a symptom to be treating in the Indian clinical setting. Dying should be as normal as birth; however, India turns out to be a country not to die as people died in vulnerable conditions. The absence of the holistic treatment in the Indian palliative end-of-life care resulted in clinicians treating the physical pain symptom alone, leaving the psychosocial and spiritual symptoms untreated, which requires special considerations alongside the physical pain symptom. The holistic assessment is a 'total care' or a 'whole person treatment,' which includes the treatment of physical pain, psychological suffering, mental disharmony, social values, and spiritual symptoms in the palliative end-of-life care. The holistic assessment is based on the unique principle; every human has different worldviews, having their own values, opinions, beliefs, and perspectives that need to be acknowledged and given special treatment until the inevitable death attack. Thus, the holistic assessment not only enhances the quality of life, but also served as a platform for the terminally ill patients can experience genuine choice and quality decision making in the face of inevitable death.